Unique Challenges in the Deceased Donation Programme in India. (July 2018) - Suriyamoorthi, Sujatha; Shroff, Sunil; Navin, Sumana; A. T, Sunitha; Pathinathan, Periyanayagam; Ranjithkumar, Ragavan; Rajasekar, Jayanalini
Abstract : Introduction: In 1994 the Government of India passed the Transplantation of Human Organs Act (THOA) that legalized the concept of brain stem death, making possible organ transplants from brain dead donors. According to THOA, two sets of brain stem tests are performed at 6 hours interval and families are usually approached for organ donation after 1st brain stem death certification. Donating a loved one's organs who has just been declared dead is an extremely difficult decision to make and can be time consuming. Continuing medical care of such patients depends on the decision of family members. ICUs in India are constantly challenged and face ethical dilemmas by not being able to switch off ventilators when families are unable to make decision or do not want to consent for organ donation. This is because the laws on definition of death are not uniform in India. Materials and Methods: In February 2010 MOHAN Foundation entered into a Memorandum of Understanding (MoU) with Rajiv Gandhi Government General Hospital, Chennai to place its trained transplant coordinators to facilitate deceased donation programme. From February 2010 to November 2017, 241 brain deaths were certified in the hospital. Families of 234 brain dead patients were approached for organ donation out of which 153 families said "yes" to organ donation (conversion rate 65%). The remaining 81 families did not consent for organ donation due to various reasons such as not believing in the concept of 'brain stem death', prolonged grief, religious beliefs, procedural time taken for donation process since the majority of them were medico-legal cases. The 2nd set of brain stem tests was not performed on these 81 persons as the treating doctors/hospitals were not clear on withdrawing ventilator support when the patient is found to be brain dead. All these patients were kept on prolonged ventilator support until circulatory arrest happened. Discussion: Continuing ventilator support to such brain dead persons brings up many ethical dilemmas mainly the priority of care – the brain dead person/the grieving family/another critically ill patient whose life is at greater risk. By prolonging ventilator support for such patients aren't we prolonging the death/dying process of the individual? Would the family's decision have been respected if they are paying medical bills? As number of ventilators is always very limited in public hospitals, shouldn't they be made available to other patients who are expected to recover from their illnesses? Conclusion: In India the definition of death appears in 3 different legal frameworks – Indian Penal Code, 1860, Registration of Births and Deaths Act, 1969, Transplantation of Human Organs Act, 1994. This has resulted in confusion about turning off ventilator when families do not consent to organ donation. It is imperative that India brings in a legal provision like USA's Uniform Determination of Death and have brain stem death delinked from organ donation. Rajiv Gandhi Government General Hospital, Chennai, India.